2017
DOI: 10.1021/acsnano.6b07302
|View full text |Cite
|
Sign up to set email alerts
|

Competition between Bending and Internal Pressure Governs the Mechanics of Fluid Nanovesicles

Abstract: Nanovesicles (∼100 nm) are ubiquitous in cell biology and an important vector for drug delivery. Mechanical properties of vesicles are known to influence cellular uptake, but the mechanism by which deformation dynamics affect internalization is poorly understood. This is partly due to the fact that experimental studies of the mechanics of such vesicles remain challenging, particularly at the nanometer scale where appropriate theoretical models have also been lacking. Here, we probe the mechanical properties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
201
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 86 publications
(224 citation statements)
references
References 44 publications
23
201
0
Order By: Relevance
“…We found that vesicles isolated from RBCs after 2 h of incubation are significantly softer than after longer incubation times, whereas they do not vary significantly between 20 h and 35 days (Figure A). Further, we find that there is a large difference in the size of vesicles: after 2 h, R 0 = 35 ± 1 nm, after 20 h, R 0 = 85 ± 3.5 nm and after 35 d: R 0 = 59 ± 3 nm (Figure B), with R 0 the original vesicle radius before adhesion assuming surface area conservation . This suggests that different vesicle generation mechanisms previously suggested theoretically, dominate at different incubation times.…”
Section: Resultssupporting
confidence: 57%
See 4 more Smart Citations
“…We found that vesicles isolated from RBCs after 2 h of incubation are significantly softer than after longer incubation times, whereas they do not vary significantly between 20 h and 35 days (Figure A). Further, we find that there is a large difference in the size of vesicles: after 2 h, R 0 = 35 ± 1 nm, after 20 h, R 0 = 85 ± 3.5 nm and after 35 d: R 0 = 59 ± 3 nm (Figure B), with R 0 the original vesicle radius before adhesion assuming surface area conservation . This suggests that different vesicle generation mechanisms previously suggested theoretically, dominate at different incubation times.…”
Section: Resultssupporting
confidence: 57%
“…Subsequently, we quantified the shape of EVs by measuring the height over the radius of curvature. From this data, we calculated the unperturbed radius of the vesicles (Figure S1B, Supporting Information), assuming surface area conservation . Figure S1 (Supporting Information) shows that the size distributions of vesicles as determined by atomic force microscopy (AFM) imaging are generally similar to those obtained from NTA.…”
Section: Resultsmentioning
confidence: 79%
See 3 more Smart Citations